2016
DOI: 10.1097/bpo.0000000000000509
|View full text |Cite
|
Sign up to set email alerts
|

Bent Telescopic Rods in Patients With Osteogenesis Imperfecta

Abstract: Level III-retrospective review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 12 publications
1
19
0
1
Order By: Relevance
“…The mean time to rod bending was 4.0 years (range 0.9-8.2 years). 17 We confirmed this mode of failure, as we found that 41% (n=7) of the 17 rods that failed to expand had bent. Transcortical migration due to proximal femur deformity, normally described in RRs with progressive deformity, occurred with one FD rod after initial central placement subsequent to proximal femur stress fracture.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The mean time to rod bending was 4.0 years (range 0.9-8.2 years). 17 We confirmed this mode of failure, as we found that 41% (n=7) of the 17 rods that failed to expand had bent. Transcortical migration due to proximal femur deformity, normally described in RRs with progressive deformity, occurred with one FD rod after initial central placement subsequent to proximal femur stress fracture.…”
Section: Discussionsupporting
confidence: 69%
“…This confirms the findings of previous studies showing higher complication rates with the use of static rods. 2,9,[15][16][17] The main complication in the RR group was distal deformity, which occurred when the rod was outgrown (86% of complications in this group). This occurred despite bisphosphonate therapy.…”
Section: Discussionmentioning
confidence: 99%
“…We attributed this difference to specific characteristics of other rods, which presented, in some cases, as robust fixation mechanisms on the distal portion, including intra-articular fixation of the knee; the same mechanism was not present for proximal fixation. 14 , 25 , 37 , 38 The TIR involves transchondral suturing for proximal fixation and a thread for distal fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Common reasons for femoral FD nail revision included femoral fracture, bending of the rod, and proximal rod migration. [ 6 , 7 ]…”
Section: Discussionmentioning
confidence: 99%